Komodifikasi Kemiskinan Dalam Pertelevisian Indonesia Pada Acara "Uang Kaget" - Tarihoran, Gabriel; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This research aims to analyze and explain how the reality TV program "Uang Kaget Lagi" exploits the poverty of its participants to create content for a television show that generates fame and profit for the media corporation itself. "Uang Kaget Lagi" is a Reality Show where an individual attempts to spend Rp12,000,000.00 within a 30-minute time limit. This research employs a qualitative descriptive approach and is supported by framing analysis methods to provide a detailed overview and explanation of the commodification of poverty within the "Uang Kaget Lagi" program. The study is grounded in Noam Chomsky's theory of propaganda. It reveals how television constructs a program that ostensibly offers assistance to impoverished individuals but has ulterior motives of gaining popularity and significant profits for the media corporation.